CHARISMA AND LEADERSHIP IN THE WORKS OF NORBERT ELIAS - Šņitņikovs, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Norbert Elias has used the concept of charisma to explain the phenomena of rule, leadership and group domination. In developing his interpretation of charisma, he critically analyzed Max Weber’s texts and applied it within his developmental, processual and figurational approach. He derived from the works of Weber the concept of group charisma and interpreted it as a universal social phenomenon. Elias considered charismatic leadership as a social situation, in which a leader’s individual charisma is fused with group charisma. Individual and group charisma are explained partly as social and psychological phenomena of individual and collective identities and partly by historically determined belief systems. Linking charisma to identity brings Elias close to Durkheim’s conception of religion. In Elias’s interpretation, the phenomenon of charisma is related to idealized individual and collective self-images. Manifestations of charismatic claims on the group level, on the one hand, are attributions to one’s group the qualities of special grace and self-praise, and on the other hand, the prejudiced attitudes to other, excluded groups. The phenomena of group charisma and group disgrace are observable in the established-outsiders power relationships. Elias’s interpretation of charisma complements the existing conceptualizations in social psychology and sociology.